Investigating VR sketching in automotive concept design: advancing spatial, environmental and operational fidelity - Charlie Ranscombe; Keun Lee; Jo Kuys (Design Science)
VR sketching tools have matured to a practical level, enabling use across various 3D design disciplines. Studies into VR sketching in design report beneficial affordances but are based on brief testing of tools in simulated tasks. Consequently, there is a knowledge deficit in understanding how to effectively integrate VR sketching into design projects. We address this gap with a case study on the sustained use of VR sketching in 10 automotive concept design projects over 10 months. In analysing designers’ logbooks, which captured design development, and post-study reflections, we show how the affordances of VR sketching outlined in literature manifest in practice. Specifically, we show how and when designers can exploit the precedence of 3D geometry embodied in VR sketches to advance the design process in terms of several dimensions of design fidelity. We highlight where process advantages are realised through (1) increased spatial fidelity, reducing the time required to iterate 2D sketches, (2) operational fidelity supporting dynamic testing of concept functionality via animation and (3) environmental fidelity supporting contextualising components and storytelling. As such, our findings highlight how and when practitioners can realise the comparative benefits of VR sketching alongside traditional sketching and 3d modelling during the concept design process.